Charismatic Species as Indicators of Plastic Pollution in the Río de la Plata Estuarine Area, SW Atlantic - González Carman, Victoria (2021)
Marine plastic pollution is projected to increase globally in the next few decades.This holds true for South America where the number of species that interacts withplastics is increasing. In this study, we explore for the first time the potential of certaincharismatic species of marine turtles, mammals and seabirds as indicators of plasticpollution in the Río de la Plata (RdP), one of the largest and most important estuarineareas of the Southwest Atlantic. Through a revision of published studies integratedwith unpublished data, we summarize studies on the interaction of charismatic marinespecies with plastics in the region and evaluate their role as indicators of plasticpollution in the RdP based on aspects of their local ecology and key attributes (i.e.,biological/ecological, methodological, and conservation attributes) of indicator species.We found that at least 45 charismatic marine species interact ?whether by ingestionor entanglement? with plastics in the region. Eight of these species were selected aspotential indicators given their occurrence, probability of sampling and interaction withplastics in the RdP, namely: Chelonia mydas, Caretta caretta, Dermochelys coriacea,Pontoporia blainvillei, Arctocephalus australis, Otaria flavescens, Larus dominicanus,and Spheniscus magellanicus. The species shared some key attributes of indicatorspecies, e.g., they are relatively well studied, but differed in critical aspects such astheir home range and mobility. We discuss whether the species? attributes are strengthsor weaknesses according to the available knowledge on their ecology in the RdP, andpropose a multispecies indicator of plastic pollution given that those strengths andweaknesses can be compensated among species. Monitoring plastic pollution througha combination of species would enable a better understanding of plastic pollution in thisrelevant area.